A CRITICAL REVIEW ON ANTI-HYPERTENSIVE ACTION OF ALLIUM SATIVUM (AYUSHDHARA, 2020)
In twenty first century we are living in an age of revolution which has significantly changed our lifestyle. Due to the rapid modernization, people are leading towards more stressful life. As a consequence, human race is suffering from various problems grouped under a common umbrella of ‘Lifestyle disorders’. Hypertension is one of the widespread lifestyle disorders. About 26.4% of the world adult population in 2000 had hypertension and 29.2% were expected to have this condition by 2025. India is considered as global capital of hypertension.Increased blood pressure i.e., hypertension has been globally acknowledged as most prevailing risk factor for life threatening cardiovascular diseases. Ayurveda is a science of life and oldest medical science as well. The principle focus of Ayurveda is on maintaining good health and adopting a healthy way of life. In spite of number of available antihypertensive drugs in modern medicine; overall percentage of patients suffering from hypertension is rising sharply. Almost 25 centuries ago, Hippocrates, the father of medicine, stated “Let food be thy medicine and let medicine be thy food”.In this article we have collected data from various researches carried out at national and International institutions on Allium sativum and its antihypertensive property. This review emphasizes on antihypertensive action of worldwide most commonly used food item with medicinal properties Allium sativum i.e., Garlic, it’s appropriate doses, contraindication, untoward effects and probable mode of action. From the above review we can say that appropriate use of Allium sativum can control hypertension up to certain extent.